(In)variability of Attachment in Middle Childhood: Secure Base Script Evidence in Diary Data. Issue 4 (20th November 2014) - Bosmans, Guy; Van de Walle, Magali; Goossens, Lien; Ceulemans, Eva
<x content-type="archive" xml:space="preserve">Abstract</x> Secure attachment is characterised by a secure base script regarding the attachment figure as a source for support. Having such a cognitive script should affect the stability of state attachment. Specifically, incongruent attachment-related information should get assimilated to this secure base script, leading to state attachment scores that hardly fluctuate. For children without a script, state attachment should vary depending on the quality of attachment-related interactions. Two diary studies were carried out in 9- to 13-year-old children. Results suggested that with assimilation: (1) securely attached children fluctuated less in their daily attachment-related appraisals; (2) fluctuations were related to conflicts with mother; (3) this relation was stronger for less securely attached children. Consequently, these studies further support the secure base script hypothesis and provide insight into the interplay of trait and state components of attachment-related appraisals.